PERFORMA AYAM ISA BROWN UMUR 99-103 MINGGU YANG DIBERI RANSUM KOMERSIAL DENGAN SUPLEMENTASI TEPUNG KULIT KERANG - Febryanti F. A.; G. A. M. K. Dewi; I G. Mahardika (Animal Science Study Program, Faculty of Animal Husbandry, Udayana University, 2020)
This study aims to determine the performance of Isa Brown chicken aged 99-103 weeks who were given a commercial ration with seashell flour supplementation. The Research held in Pesedahan Village, Manggis District, Karangasem, Bali. The design used was a Completely Randomized Design (CRD) with 4 treatments and 5 replications, and each replication used 5 chickens. The treatment given is; layer chickens were given commercial rations without additional seashell flour (A), chickens were given commercial rations and 1% seashell flour (B), chickens were given commercial rations and 2% seashell flour (C), chickens were given commercial rations and 3% seashell flour (D). The variables observed were feed consumption, hen-day production, egg weight, feed conversion and Income Over Feed Cost (IOFC). The results of this study indicate that the administration of 1%, 2%, and 3% shellfish flour in commercial rations gives results that have no significant effect (P> 0.05) on ration consumption, ration consumption, hen-day production, egg weight, conversion ration but out can increased the Income Over Feed Cost (IOFC) compared to control treatment (A). Based on the results of this study it can be concluded that the administration of seashell flour by 1%, 2%, and 3% gives the same results on ration consumption, hen-day production, egg weight and ration conversion but can increase the Income Over Feed Cost. Keywords: performance, Isa Brown, seashell flour